The Influence of Customer Experience on Customer Loyalty Sate Rembiga Goyang Lidah with Customer Satisfaction as a Mediation Variable - Imam Gazali Gazali; Baiq Handayani Rinuastuti Gazali (CV. Abhinaya Indo Group, 2026)
The increasingly fierce competition in the culinary industry in Mataram City encourages business actors to not only focus on product quality, but also on the overall customer experience. This study aims to analyze the influence of customer experience on customer loyalty in Sate Rembiga Goyang Lidah with customer satisfaction as a mediating variable. The approach used is a quantitative research of the causal associative type with a survey method. The sample of 100 respondents, namely customers who have made purchases at least twice and are domiciled in Mataram City, were selected using the purposive sampling technique. Data was collected through a questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SmartPLS 4.0 application. The results showed that customer experience had a positive and significant effect on customer loyalty (channel coefficient = 0.278; p = 0.033) and customer satisfaction (channel coefficient = 0.803; p = 0.000). Customer satisfaction was also shown to have a positive and significant effect on customer loyalty (path coefficient = 0.605; p = 0.000). Furthermore, customer satisfaction was proven to mediate the relationship between customer experience and customer loyalty (indirect path coefficient = 0.486; p = 0.000). An R-square value of 0.714 for customer loyalty indicates the model's strong predictive power. This research emphasizes that the strategy of improving customer experience holistically, including sensory, emotional, and social dimensions is the key to forming customer loyalty in local culinary MSMEs.